MULTIPLE IMPACT ANALYSIS OF PILING WORK ON HIGH WAY PROJECTS USING THE EVM METHOD - Mik Wanul Khosiin; Tatang Ari Gumanti; Ali Muktiyanto; Widi Hidayat (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
A toll road is one of the economic growth facilities of a country, Indonesia in the last seven years has succeeded in building 1900 km and one of them is Trans-Java. The Gempol-Pasuruan section-2 toll road project is a densely populated route and there are many intersections in the form of roads and rivers so there are many overpass or underpass structures in the project. Although the bridge structure is a sub-project of the main road, if the productivity does not perform well, it will have a significant impact on the overall progress. Therefore, this study wants to analyze the multiple impacts of one of the critical works of the bridge project, such as the pilling work on the total toll road progress through the earn value management (EVM) method. EVM is a technique that is quite popular both among practitioners and academics; however, analysis of complex projects (main projects-sub projects) has never been carried out in-depth and it will be a unique challenge in this study. There are four steps in this research, the first step is project scheduling in which the engineer can use the previous database to prepare the work breakdown structure (WBS), work sequences, and project duration. The second step is the critical path process, at this stage, a slack analysis is carried out for each activity, and setting a network diagram to generate critical paths for the toll-bridge project. Resource management is the third step that involves a lot of documents from the market and internal databases, starting with assigning resources, inputting quantity and unit prices, and doing the leveling process so that the supply chain runs well. The last step is the earn value process, at this stage, the engineer only needs to input the project progress, set the baseline, and finally get the earn value project and project performance index consisting of SPI (schedule) and CPI (cost). Finally, after going through several stages of research, it has been proven that the pilling work is on a critical path and several scenarios must be carried out to maintain its productivity. Then, the average SPI value is 0.94 < 1, while the SPI value is 1 which means that the Gempol-Pasuruan section-2 toll road project is experiencing delays and is within the project budget. In conclusion, the application of the EVM method on MS. Project 2013 is able to evaluate complex projects well and several potential technologies can also be considered in further study to improve the performance.